Detecting underground structures in vegetation indices: MSR, RDVI, OSAVI, IRG, time series using histograms - Melillos, George; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G. (My University, 2020)
This paper focuses results obtained from a field spectroscopy campaigns for detecting underground structures. A number of vegetation indices such as the Modified Simple Ratio (MSR), Renormalized Difference Vegetation Index (RDVI), Optimized Soil Adjusted Vegetation Index (OSAVI) and Red Green Ratio Index (IRG) were utilized for the development of a vegetation index-based procedure aiming at the detection of underground military structures by using existing vegetation indices. The measurements were taken at the following test areas such as: Area (a) vegetation area covered with the vegetation (barley), in the presence of an underground military structure and Area (b) vegetation area covered with the vegetation (barley), in the absence of an underground military structure. For this purpose was using histograms to obtain useful information about Vegetation Indices spectral behaviors and to compare the two testing areas.
Keywords: Field Spectroscopy; Histograms; IRG; MSR; OSAVI; RDVI; Remote Sensing; Vegetation Indices